Polymeric objects switchable between two shapes - Liu, Yue (2021)
As the ongoing trend of developing smart materials that can reversibly switch geometry stimulated by environmental control addressed increasing attention in many research fields, especially for biomedical or soft robotic applications. Shape-memory polymers (SMPs), which can change shape, stiffness, size, and structure when exposed to an external stimulus, are intensively explored as encouraging material candidates for achieving multifunctionality, and for miniaturizing into micro-components to expand the applications. Besides, the geometrical design has gained growing attention for creating engineering applications, such as bi-stable mechanisms, and has the potential to be explored by implementing SMP for new functions. In this context, this thesis aimed to develop smart micro-/nano-objects based on SMP and explore new functions by geometrical design using SMP. Here, two types of stimuli-responsive objects capable of one-way temperature-memory effect (TME) or free-standing reversible actuation e.g., micro/nanofibers (i) and microcuboids (ii) at different aspects were explored. [...]
Kumulative Dissertation
Keywords: Hochschulschrift